"Who am I?": the inluence of palliative care on the identity formation of health professionals - Eloisa Cristina Gonçalves; Renato Soleiman Franco; Diego Lima Ribeiro; Gabriela Maria Arenhart Soares; Suelen Miná Valadares de Almeida Silva (Espaço para a Saúde - Revista de Saúde Pública do Paraná, 2026)
Palliative care elevates care to a human perspective of affection and emotions that can influence our identities. The objective of this project was to understand how caring for end-of-life patients influences how the individual sees themselves as a subject and a professional. The instrument used was the Rich Picture, a pictorial representation (drawings) to capture the individual’s perspective on a situation. The ten participants of the multidisciplinary team were invited to draw a real situation that occurred during the care of a patient. The results address care and the encouragement of reflection; the importance of connection to give meaning to the profession; the conflicts generated by teamwork; personal and professional development; and care that generates uncertainty, guilt, and frustration. Thus, being a professional encompasses values, beliefs, and behaviors that help in elaborating how to give meaning to the profession